Development, validation, and reliability testing of the College Perspectives around Food Insecurity survey - Jennette Kilgrow; Elyce Gamble; Amanda Meier; Kyle Lyman; Andrea Barney; Cade Kartchner; Paola Martinez; Kanae Lee; Carol Mathusek; Kelly Ang; Brooke M. Green; Jinan Banna; et al. (PLoS ONE, 2025)
The objective of this study was to develop and to test the validity and reliability of a survey aimed to evaluate internal and external factors associated with college food insecurity. Researchers used a mixed methods approach to evaluate the College Perspectives around Food Insecurity survey. Survey items were constructed from interview data and assigned a social cognitive theory concept (environment, personal, or behavior). Two rounds of expert reviews established content validity (Round 1, n = 3; Round 2, n = 2). Researchers evaluated face validity through two rounds of cognitive interviews with college students 18+ years old (Round 1, n = 9; Round 2, n = 16) and tested survey reliability (n = 105). Researchers used descriptive statistics, test-retest reliability statistics, and Cronbach’s alpha scores for data analysis. The initial survey contained 143 items. After feedback from expert reviewers and cognitive interviews, the final survey contained 99 items. Test-retest reliability was 0.99, and Cronbach’s alpha scores were 0.74 for environment, 0.47 for personal, and 0.39 for behavior. The College Perspectives around Food Insecurity survey can be used to better understand internal and external factors associated with food insecurity in college students, which can inform interventions aimed at assisting this population.